Chemical vapor deposition and characterization of two-dimensional molybdenum dioxide (MoO2) nanoplatelets. (12th October 2018) - Vorobeva, Nataliia S; Lipatov, Alexey; Muratov, Dmitry S; Sinitskii, Alexander
Abstract: We report on the chemical vapor deposition synthesis of MoO2 nanoplatelets by sublimation of MoO3 and its reduction in a hydrogen atmosphere at 750 °C. When grown on Si/SiO2 substrates, the platelets primarily assume a rhomboidal shape and have thicknesses ranging from several to tens of nm. The morphology of MoO2 crystals was found to depend on the chemical nature of substrates. MoO2 platelets on Si/SiO2 were characterized by a number of microscopic and spectroscopic techniques, and the electrical measurements revealed the metallic nature of their conductivity averaging at 2400 ± 1000 S cm −1 . Raman spectroscopy of MoO2 platelets on graphene indicates their strong hole injection property. Small thickness, planar morphology, high chemical stability and metallic conductivity of ultrathin MoO2 platelets make them potentially interesting for integration different other two-dimensional materials in a variety of electronic structures and devices.